Exploring Secondary Level Students' Participation in English Classroom in Nepal: A Literature Review - Upadhyay, Mathura Prasad (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
This literature review delves into the dynamics of classroom participation among secondary level students' in English as a Foreign Language (EFL) settings within Nepal. Traditional teaching methods often foster passive learning, impeding both engagement and comprehension. Thus, this study aims to explore the factors and strategies for fostering active participation, crucial for academic performance and the development of social and extracurricular skills among secondary level students. Understanding the dearth of research in this area, the study investigates strategies to bolster classroom engagement, particularly emphasizing, Socio-cultural theory, motivational theory, critical pedagogy theory, peer interactions alongside explicit instruction. This study adopts a descriptive qualitative methodology, employing library research methods as its primary approach. Qualitative analysis unravels the multifaceted nature of participation, advocating for inclusive and supportive classroom environments. It underscores the necessity for teachers to adapt their approaches to accommodate diverse student backgrounds, thereby fostering active engagement. The findings include collaborative learning experience, integration of language learning strategies, creating a supportive classroom environment and embracing a multidimensional approach in leaning process. By accentuating socio-cultural factors and classroom dynamics, this study enriches pedagogical practices and motivates English language learners to participate actively. In conclusion, the research contributes significantly to the understanding and enhancement of classroom participation dynamics in EFL settings, ultimately facilitating more effective and motivating language learning experiences for learners.